Calculation of Plane Contact Heating under Steady-State and Transient Conditions on the Basis of One-Dimension Model of Temperature Field - D. A. Gerasimovich; Y. A. Klimovich; M. A. Mishkina; G. G. Ezenkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes one-dimension model of temperature field with the purpose to calculate plane contact heating under steady-state and transient conditions. The numerical algorithms have been developed to calculate contact temperatures. These algorithms are based on a separate solution of differential equations of electromagnetic and temperature fields. The finite difference method and numerical and analytical method for steady-state conditions have been applied in the calculations. Distribution of temperature along the length of plane and knife-type contacts at various moments of short-circuit conditions has been obtained. The investigations have shown that current conducting parts determine contact temperature in the case of steady-state conditions. In the case of transient conditions there is a possibility of significant over-heating of contact connections.